Comparison of Surgical and Oncological Outcomes between Laparoscopic and Open Surgeries in Patients with Stage IA1 Cervical Cancer - Shinichi Togami; Nozomi Furuzono; Mika Mizuno; Hiroaki Kobayashi (Gynecology and Minimally Invasive Therapy)
Objectives: Laparoscopic surgery improves patient quality of life; however, its utility in stage IA1 cervical cancer remains debatable. This study aimed to compare the surgical and oncological outcomes of laparoscopic versus open surgery in patients with stage IA1 cervical cancer. Materials and Methods: Thirty-four patients, including 20 who underwent laparoscopic surgery and 14 who underwent open surgery, were enrolled in this study. The surgical and oncological outcomes were compared between the laparoscopic and open surgery groups. Results: No statistically significant differences were observed between the laparoscopic and open surgery groups in terms of median age, body mass index, final pathological type, the presence of lymphovascular space invasion, and operation time. Patients who underwent laparoscopic surgery had significantly lower blood loss (38 vs. 170 mL, P < 0.001) and shorter postoperative hospital stay (5 vs. 7.5 days, P < 0.0001) than those who underwent open surgery. Oncological recurrence was observed in only one patient in the laparoscopic group (vaginal cuff). The 3-year recurrence-free survival rate was 94.7% and 100% for the laparoscopic and open surgery groups, respectively, with no statistically significant difference. Conclusion: Laparoscopic surgery resulted in reduced blood loss and shorter hospital stay, with oncological outcomes comparable to those of open surgery in patients with stage IA1 cervical cancer. These findings highlight the potential benefits of laparoscopic surgery in improving surgical outcomes for patients with stage IA1 cervical cancer.